2021
DOI: 10.1186/s12888-021-03109-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress associated with the COVID-19 pandemic and suppression measures during the first wave in Belgium

Abstract: Background The COVID-19 pandemic and subsequent suppression measures have had health and social implications for billions of individuals. The aim of this paper is to investigate the risk of psychological distress associated with the COVID-19 pandemic and suppression measures during the early days of the lockdown. We compared the level of psychological distress at the beginning of that period with a pre-pandemic health survey and assessed the psychological effects of exposure to the COVID-19 pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 49 publications
6
69
4
1
Order By: Relevance
“…We did not investigate the effect of loneliness and low social support on mental health, but a study among young Belgium people found these factors to be the main predictors of mental distress [49]. Another study in Belgium found psychological distress to be associated with the consequences of the Covid-19 pandemic and containment measures [50]. Furthermore, Polish respondents reported the highest prevalence of depression and the highest new incidence of panic disorder (presumed diagnosis based on positive screening results).…”
Section: Discussionmentioning
confidence: 97%
“…We did not investigate the effect of loneliness and low social support on mental health, but a study among young Belgium people found these factors to be the main predictors of mental distress [49]. Another study in Belgium found psychological distress to be associated with the consequences of the Covid-19 pandemic and containment measures [50]. Furthermore, Polish respondents reported the highest prevalence of depression and the highest new incidence of panic disorder (presumed diagnosis based on positive screening results).…”
Section: Discussionmentioning
confidence: 97%
“…Preventive measures and social distancing requirements have been developed and mandated to contain the spread of the virus and are still ongoing in specific regions [33]. College students have faced a number of challenges, such as sudden closures of university dormitories, cancellation of all in-person instruction and field placements (e.g., practicums and internships), the loss of off-campus jobs that require in-person contact, lack of in-person social support from peers and instructors, and a dramatic reduction in outdoor physical activities [34]. According to Lazarus [35], perceived stress is experienced subjectively by an individual, who might identify an imbalance between the demands placed on them and the available resources to deal such demands.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the spread of the coronavirus and the confinement measures that have been taken to prevent this spread may impact the mental health of the general population [12,[14][15][16]. Indeed, researchers in many countries found that the mental health of the population has deteriorated since the outbreak of the virus [17][18][19][20][21][22]. So far, the relationship between health literacy and mental health during the COVID-19 pandemic has solely been explored in three studies, the results of which suggest a buffering effect of health literacy [23][24][25].…”
Section: Introductionmentioning
confidence: 99%